The Cinematic Gaze and Kuttner's "Man with a Movie Camera". Issue 3 (January 2018) - Telotte, J. P.
Abstract : This essay examines how a modernist sense of space, often linked to the movies, made its way into sf pulp literature during the pre-war and early postwar period. It focuses on Henry Kuttner's Tony Quade stories with their unlikely protagonist, a futuristic cinematographer, who while shooting films throughout the solar system must use his technological prowess to cope with outer space's hazards and to fashion movies that, despite film's limitations, afford a modernist sense of what is termed "the real thing." Using Francesco Casetti's analysis of cinematic modernism, the essay shows how film and its gaze helped codify "outer space" as part of sf's modernist experience.